POLA INTERAKSI SOSIAL PADA SD NEGERI PAKIS V SURABAYA DI MASA PANDEMI COVID-19 - Ainnur Ristyanti; Rossa Ilma; Finna Gabriella (DAS Institute, 2022)
Covid 19 and social processes have a close relationship with social interaction during this conflict pandemic. A lot has happened as a result of this pandemic. Social shifts include social interactions in the elementary school environment. The purpose of this study was to determine the pattern of social interaction of students at SD Negeri Pakis V Surabaya during the Pandemic Period. This study used qualitative research methods. The data sources of this research are primary data that comes from informants directly and secondary data from this research is derived from literature studies obtained from books, journals, and internet articles. Then the data collection techniques used in this study were interviews, observations, and documentation. Furthermore, the data analysis techniques used in this study were interactive model data analysis techniques. The results of this study found that six dimensions in the theory of Interaction Process Analysis in WhatsApp Groups have been passed in every conversation theme discussed. This shows that group interaction theory can also be applied to interactions through online media. The phases that are passed in online communication are almost the same as the phases carried out in conventional communication with regard to academic/theoretical aspects or methodologies and suggestions for practical aspects.